Discipline-specific language challenges faced by Chinese music student-teachers on a UK master’s programme - Li, Hang; Haddon, Elizabeth (Frontiers in Education, 2025)
This paper presents findings from a subunit study of doctoral research carried out by the first author at the University of York, UK, investigating the language challenges faced by Chinese student-teachers on their English-taught MA music education programme. While previous research has addressed language challenges for international students and teacher trainees, these remain underexplored in music-related studies. Using a qualitative case study approach, data were collected through a questionnaire survey of student participants and semi-structured interviews with teaching staff on the focused MA music education programme. Findings indicate that these non-native music teacher trainees struggle with academic writing, music terminology, and verbal communication skills in instrumental/vocal teaching contexts, which affect their engagement with both theoretical and practical modules on their English-taught programme. Limited language proficiency influences their confidence in academic and teaching practices, which potentially hinders their pedagogical development as future instrumental/vocal teachers. The study highlights the need for discipline-specific language support tailored to the demands of the degree programme, contributing to the growing literature on international student experiences and the linguistic needs of music education teacher trainees who speak English as an additional language.